Mortalidad de la fauna silvestre por atropellamiento en la carretera Loja-Malacatos-Vilcabamba - Iñiguez López, Pablo Andrés (2022)
Roads are essential communication routes for the development of a region; however, they are a source of pressure for wildlife, directly due to roadkill. Wildlife roadkill is mainly due to factors such as speed, vehicular flow, and the type of road infrastructure. This study evaluated wildlife roadkill caused by vehicles on the Loja-Malacatos-Vilcabamba road (E682) in the province of Loja. This 41.6 km long, two-lane paved road is located in a close-by area to the Podocarpus National Park. The study was conducted from April to June 2022, where 16 car trips were made at a speed range of 50-60 km/h, covering a total of 666 km in 50 sampling days. Field data was collected through an open-source platform with the help of geographic information management software (Epicolect5). A total amount of 60 roadkill individuals were found, belonging to 20 species, 19 families, and 4 classes. From the class Aves (9 families, 9 species), the class Mammalia (5 families, 6 species), the class Reptilia (4 families, 4 species), and the class Amphibia (1 family, 1 species). The species with the highest incidence of roadkill found were the opossum Didelphis marsupialis (n=17; 28.33%) and the bird Furnarius leucopus (n=8; 13.33%). The roadkill rate for 41.6 km of road was 1.44 Indv/Km. Mammals obtained the highest per day roadkill rate with a 0.053 Indv/Km/day. The results show that the agricultural land presented the highest number of roadkill events, with 37 individuals sampled (61.67%). The vegetation coverage showed significant differences in the number of roadkill individuals; the Kruskal Wallis analysis shows a significant difference (p<0.0052). The variable "traffic volume" did not show a significant influence on the presence of individuals hit by vehicles, Pearson correlation presented a weak negative correlation (0.549). Three hotspots were identified (two in agricultural land and one in the anthropic zone), where mitigation measures such as speed reducers, luminous reflectors, and signage are suggested to reduce wildlife mortality due to roadkill. Key words: Mortality, land cover, hotspot, mitigation